Centre of Agri-Knowledge – a Web-Based Integration of Information and Decision Support Systems for Agriculture - Dövényi-Nagy, Tamás (Acta Agraria Debreceniensis, 2006)
The University Debrecen Centre of Agricultural Sciences acts as the centre and co-ordinator of agrarian higher education and consultation in the eastern region of Hungary. New internet technologies afford new chances to accomplish the institute’s mission to develop agriculture, environment and countryside in the area. As the main framework of integrated e-learning, e-business and research in the agrifood sector the development of an internet portal, the „Centre of Agri-knowledge” (CAK) has been started in the recent past. To support our students and education, to stay continuous in touch with our agricultural engineers we consider very important to build internet communities, where students, farmers, traders and researchers can share their knowledge and experience. In Europe same as in Hungary agriportals born and disappear continuously. Although CAK is still in its early stage of development, its comprehensiveness, professional backend and the experience of the Centre of Agricultural Sciences guarantee a new standard of online services in the Hungarian agrifood sector